Peranan Pengadilan dalam Pelaksanaan Putusan Arbitrase Internasional - Safrina Safrina (Universitas Syiah Kuala, 2011)
ABSTRACT: Arbitration is a forum for dispute resolution outside of court that has been chosen by the businesses. One of benefits and advantages has by the arbitration body is the force of law from a final decition (a decition the final level) and binding (binding both parties to the dispute). In the implementation of international award, Indonesia has ratified New York Convention in 1958 through Presidential Decree No. 34 of 1981 that authorizing the execution of foreign arbitration in Indonesia. In addition, through Act No. 30 of 1999, requires that the courts play an important role in the enforcement of international arbitration. The international award can be executed in Indonesia after it being eksekuatur from the chairman of the Central Jakarta District Court. Role of Courts in the Implementation of the Decisions of International Arbitration